Biosorption of Pb2+, Ni2+ and Cu2+ ions from aqueous solutions by L-cystein-modified montmorillonite-immobilized alginate nanocomposite. Issue 38 (14th August 2016) - Mittal, Alok; Ahmad, Rais; Hasan, Imran
Abstract: In this study, L-cystein-modified montmorillonite (MMT)-immobilized sodium alginate biopolymer-based nanocomposite was synthesized using solution casting method. The synthesized material was characterized by X-ray diffraction, FTIR, TGA-DTG, scanning electron microscopy and transmission electron microscopy techniques. The material was further evaluated for the removal of heavy metal ions like (Pb 2+, Ni 2+ and Cu 2+ ) from aqueous solutions. The effect of various parameters such as pH, agitation time, initial metal ion concentration, temperature and adsorbent dose on the extent of adsorption was investigated. The equilibrium data obtained by experiments were well analysed by four isotherm models, and the results are well fitted with Langmuir model at 50°C, and a maximum adsorption capacity ( q m ) 100.00, 111.11 and 125.00 (mg g −1 ) was obtained for Cu 2+, Pb 2+ and Ni 2+, respectively. Various kinetic equations were applied to kinetic data, and the results are best found to follow pseudo-second-order kinetic model. Thermodynamic parameters of the adsorption process such as the standard Gibbs free energy change (∆ G °), standard enthalpy change (∆ H °), standard entropy change (∆ S °) were calculated, and the result showed that adsorption of heavy metals onto Alg-Cys-MMT is spontaneous and endothermic in nature.